Impact of climate change on plant nutrient dynamics and soil forming process - Dotaniya, M L; Singh, Harvir; Meena, M D; Choudhary, R L (Indian Farming, 2021)
Over the past few decades, acceleration in the human-induced changes in the climate of the Earth has become the focus of scientific and social scrutiny. The gaseous composition of the atmosphere has undergone a significant change mainly through increased industrial emissions, fossil fuel combustion, widespread deforestation and burning of biomass as well as changes in land use and land management practices. These anthropogenic activities have resulted in an increased emission of radiatively active gases, e.g., carbon dioxide (CO2), methane (CH3) and nitrous oxide (N2O), popularly known as the ‘greenhouse gases’.